Protein-enriched cassava to combat malnutrition - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Cassava is a key part of the diet of many CentraI Africans. It is easy to grow and high in carbohydrates, but low in protein from 07% to 1.6% depending on the variety. The traditional maceration or fermentation that cassava undergoes before it is...